PRODUKTIVITAS RESIN PINUS MERKUSII JUNGH ET DE VRIESE PADA KELAS UMUR DAN KETINGGIAN TEMPAT TUMBUH YANG BERBEDA - Arip Wijayanto; Nurmadina, Nurmadina (Wahana Forestra: Jurnal Kehutanan, 2021)
Pine resin production is influenced by several factors, including altitudes and the different classes of age . In addition, the productivity of pine resin is also influenced by weather and climate. The aim of study that entitled oductivity of Resin Pinus Merkusii Jungh Et De Vriese in Several Class Ages and Altitudes, was to investigate pine resin productivity in Forest Management Resort Guyangan, Perum Perhutani, based on variation of altitudes and class ages classified by Perum Perhutani. This study used resin production data that taped by quare methode from Forest Management Resort Guyangan, and then data were analysed with microsoft office excel. The result of this study showed that the highest pine resin productivity is 0.22 kg/tree/month for class age (KU) V and IV, and the lowest pine resin productivity, i.e. 0,19 kg/tree/month is for KU VII. Based on altitudes, resin productivities for 500-799 (mdpl) and 800-999 (mdpl) were 0,22 kg/tree/month and 0,20 kg/tree/month respectively. Based on this study, it can be concluded that the higher altitudes the lower pine resin productivity. Meanwile basedon the age class, the productivity of pine resin in different age class shows different values.